2013
DOI: 10.5152/akd.2013.103
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of paraoxonase-1, malondialdehyde and mean platelet volume with markers of atherosclerosis in familial Mediterranean fever: an observational study

Abstract: Our results show that PON-1 activity is lower in patients with FMF. Reduced PON-1 activity and increased MPV, independent of the oxidative stress status of these patients, may lead to increased atherosclerotic propensity in FMF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
(41 reference statements)
2
9
1
Order By: Relevance
“…Usefulness of MPV in assessment of atherosclerotic risk in cases with FMF was also investigated. In accordance with our results, most of the studies found significantly higher MPV values in FMF patients and stated that FMF is associated with increased risk of atherosclerosis [6,9,10]. MPV values were found higher even in attack-free FMF cases.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Usefulness of MPV in assessment of atherosclerotic risk in cases with FMF was also investigated. In accordance with our results, most of the studies found significantly higher MPV values in FMF patients and stated that FMF is associated with increased risk of atherosclerosis [6,9,10]. MPV values were found higher even in attack-free FMF cases.…”
Section: Discussionsupporting
confidence: 92%
“…Carotid intima media thickness, endothelial dysfunction, MPV and EAT thickness are some parameters that suggested for evaluation of increased atherosclerotic risk [3-5,7]. Familial Mediterranean fever is an inflammatory disease suggested to predispose to atherosclerosis [4-6]. The current study has found that FMF cases had significantly higher EAT thicknesses and MPV values when compared to healthy controls and EAT thickness has correlated with age of diagnosis, duration of delay in diagnosis, and MPV values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…C-Reactive Protein (CRP) is a member of Pentraxin family, which plays a key role in the innate immune response. CRP is the most sensitive acute reactant protein and its concentration increases rapidly during inflammatory processes (6)(7)(8). This protein has been shown to have prognostic value in patients with acute coronary syndromes and plays different roles in pathogenesis of atherosclerosis (7).…”
Section: Introductionmentioning
confidence: 99%